2010
DOI: 10.1186/cc9060
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-pressure variation and hemodynamic response in patients with elevated pulmonary artery pressure: a clinical study

Abstract: IntroductionPulse-pressure variation (PPV) due to increased right ventricular afterload and dysfunction may misleadingly suggest volume responsiveness. We aimed to assess prediction of volume responsiveness with PPV in patients with increased pulmonary artery pressure.MethodsFifteen cardiac surgery patients with a history of increased pulmonary artery pressure (mean pressure, 27 ± 5 mm Hg (mean ± SD) before fluid challenges) and seven septic shock patients (mean pulmonary artery pressure, 33 ± 10 mm Hg) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 39 publications
(57 reference statements)
4
62
0
7
Order By: Relevance
“…In this context it has been shown that concomitant tricuspid regurgitation is associated with underestimation of cardiac output measured by thermodilution [47]. In addition, clinically used parameters to estimate volume responsiveness seem to be unreliable in patients with right heart dysfunction [48,49]. Finally, hTEE monitoring was non-inferior to standard patient care in guiding norepinephrine treatment.…”
Section: Discussionmentioning
confidence: 98%
“…In this context it has been shown that concomitant tricuspid regurgitation is associated with underestimation of cardiac output measured by thermodilution [47]. In addition, clinically used parameters to estimate volume responsiveness seem to be unreliable in patients with right heart dysfunction [48,49]. Finally, hTEE monitoring was non-inferior to standard patient care in guiding norepinephrine treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Arterial respiratory variation is a promising clinical variable but has some shortcomings [19][20][21]. In particular, while there is a statistically significant relationship between respiratory variation and response to fluid loading, substantial individual variability limits the predictive capabilities of these metrics [22].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methods of assessing fluid responsiveness, such as central venous pressure, pulse pressure variation, and stroke volume variation, are unreliable in patients with RV dysfunction. 62,63 Elevation in plasma atrial natriuretic peptide and BNP seems to increase proportionately to the extent of RV dysfunction in patients with PH. 54,64 The traditional gold standard for the diagnosis and management of PH and RV dysfunction is pulmonary artery catheterization (PAC).…”
Section: Preload and Volume Statusmentioning
confidence: 98%